Incisional hernia rate after ileostomy closure in lateral pararectal stoma versus transrectal stoma placement: follow‐up of the randomized PATRASTOM trial - Seyfried, Steffen; Lucas, Victoria; Galata, Christian; Reißfelder, Christoph; Weiß, Christel; Kienle, Peter; Hardt, Julia (Colorectal disease, 2020)
Aim - Because damage to the rectus abdominis muscle during ileostomy placement and reversal might be a risk factor for the development of stoma‐site incisional hernia (SSIH), we hypothesized that posioning of the stoma lateral to the rectus abdominis muscle might prevent SSIH.